2009
DOI: 10.4314/gjcm.v2i1-2.47928
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude And Perception Of Epilepsy Among Traditional Healers In Uyo, Nigeria

Abstract: The poor knowledge of epilepsy among traditional healers is due to cultural prejudices and environment. The resultant deep-rooted misconceptions and myths negatively affect the attitudes and encourage traditional care with high morbidity and mortality. The objectives of the study were to assess knowledge of epilepsy among traditional healers and to determine the modalities used in the care. One hundred and seventy three traditional healers from villages/communities in Uyo were assessed for knowledge; attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
2
3
0
Order By: Relevance
“…The findings from this study seem to reinforce this misconception about the cause of epilepsy. This finding is similar to Abasiubong et al's study, which revealed that in the olden days when people had no knowledge or understanding of biomedical science, epilepsy was attributed to a spiritual or religious affliction ( 14 ). Even though there is advancement in biomedical science at this present time, people still have ancient beliefs about epilepsy as the manifestation of an evil spirit in the victim.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings from this study seem to reinforce this misconception about the cause of epilepsy. This finding is similar to Abasiubong et al's study, which revealed that in the olden days when people had no knowledge or understanding of biomedical science, epilepsy was attributed to a spiritual or religious affliction ( 14 ). Even though there is advancement in biomedical science at this present time, people still have ancient beliefs about epilepsy as the manifestation of an evil spirit in the victim.…”
Section: Discussionsupporting
confidence: 89%
“…Essentially, epilepsy is considered a means of compelling people to adhere to moral standards. Evidence from a study by Abasiubong et al ( 14 ) justifies the findings of this current study. Their study showed that 14% of the population attributed the cause of epilepsy to punishment for sins ( 14 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been linked to witchcraft, spiritual attacks, and punishment for sins by traditional healers and even university students. [8,9] There is also the belief that seizure disorder is contagious, and one can get infected by contact with the saliva from the mouth of the patients during seizure attacks. [10] These beliefs expose the child with seizure disorder to danger during a seizure episode, as they are likely to be left unattended to by both the teachers and their schoolmates for fear of getting the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have involved the knowledge, attitude and perception of various issues have been conducted worldwide (Abasiubong et al, 2009;Adediwura & Tayo, 2007;Anjum et al, 2008;Erhum et al, 2008;Tjakraatmadja et al, 2008). For instance, in India the knowledge, perception, attitude of adolescent girls towards STIs/HIV and safer sex education were done and indicated the need to implement gender-based sex education (McManus & Dhar, 2008).…”
Section: Introductionmentioning
confidence: 99%